The Implementation of the Communicative Approach in Teaching Maharah Al-Kalam at Islamic Senior High Schools: Teachers’ and Students’ Perspectives - Yusnaini Pulungan; Ediat Ediat; Yelfa Mulya; Ahmad Syihabuddin (Gunung Djati Conference Series, 2026)
This study aims to investigate: the implementation of the communicative approach in teaching Mahārah al-Kalām at Islamic Senior High Schools (MA) from teachers’ perspectives; the implementation of the communicative approach from students’ perspectives; the supporting and inhibiting factors influencing its application; and the effectiveness of the communicative approach in improving students’ speaking skills (Mahārah al-Kalām) in MA. This research employs a descriptive qualitative approach to provide a comprehensive depiction of how the communicative approach is applied in teaching Mahārah al-Kalām at Madrasah Aliyah from the viewpoints of both teachers and students. Data were collected through observation, interviews, and documentation, and were further supported by relevant literature. The analysis followed the Miles and Huberman model, data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation to produce an accurate representation of the effectiveness of the communicative approach in enhancing students’ speaking abilities. The findings reveal that the implementation of the communicative approach in teaching Mahārah al-Kalām at Madrasah Aliyah is moderately effective. Teachers act as facilitators by integrating activities such as ḥiwār (dialogue), role play, and group discussions, while students demonstrate increased confidence and fluency in speaking. Supporting factors include teacher competence, student enthusiasm, and the presence of a bi’ah lughawiyyah (Arabic linguistic environment), whereas inhibiting factors consist of limited vocabulary, shyness, and insufficient supporting facilities.